1969
DOI: 10.1002/aja.1001250202
|View full text |Cite
|
Sign up to set email alerts
|

Blood vessels and tissue space associated with the brain of the rat

Abstract: Tissues from adult Sprague-Dawley rats fixed by perfusion with buffered aldehydes for a combined study of the vascular system of the brain are described in light and electron microscopy. In these preparations lack of shrinkage prevents the formation of perineuronal and perivascular spaces. However, connective tissue stains indicate restricted tissue space along the course of small arteries and veins. In fine structure this space is found within the walls of the vessels. It consists of a tubular extension of ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
1
1

Year Published

1971
1971
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 23 publications
1
36
1
1
Order By: Relevance
“…First, there are documented anatomic differences between the cerebral arteries found in rats and those found in humans. For instance, there is a difference in wall structure (17) as well as the abundance of collateral blood flow (20). Also, the lack of mural interadventitial spaces in the rat can make this species more resistant to cerebral arterial constriction.…”
Section: Discussionmentioning
confidence: 99%
“…First, there are documented anatomic differences between the cerebral arteries found in rats and those found in humans. For instance, there is a difference in wall structure (17) as well as the abundance of collateral blood flow (20). Also, the lack of mural interadventitial spaces in the rat can make this species more resistant to cerebral arterial constriction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigators have mainly studied the intracranial venous vessels by transmission electron microscopy (TEM) (TAKAHASHI, 1968;FREDERICKSON and Low, 1969;ROGGENDORF et al, 1978). According to these studies, intracranial venules up to 20um in diameter are covered with pericytes, while those exceeding 30um in diameter are covered with cells which cannot be classified as pericytes nor as smooth muscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative explanation for the lack of vascular changes seen in our study is that rat cerebral blood vessels are somehow more resistant to this insult than the vessels of other species. Previous studies have shown that the structure of rat blood vessels is different from that of humans and other species in that the rat basilar artery does not contain interadventitial spaces, 37 which have been implicated in the development of vasospasm. 38 Our investigations were undertaken in an exhaustive efiFort to document delayed CBF changes after SAH in rats and to reproduce the morphologic changes of vasospasm that have been observed in the clinical setting.…”
mentioning
confidence: 92%